2022
DOI: 10.1039/d2sm00813k
|View full text |Cite
|
Sign up to set email alerts
|

Tubulation and dispersion of oil by bacterial growth on droplets

Abstract: Bacteria on surfaces exhibit collective behaviors, such as active turbulence and active stresses, which result from their motility, growth, and interactions with their local surroundings. However, interfacial deformations on soft...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…After 3 h of mixing, d50 was reduced to 4.4 μm, which was a full 3 times smaller than that of the sterile control group (17 μm). This suggested that the presence of bacteria may promote the dispersion of oil droplets, form droplets with smaller particle sizes, and enhance the interaction between kaolinite and oil droplets . However, after 24 h, the droplet size in the sample started to increase and d50 increased to about 5.5 μm, which was still smaller than d50 at 1 min (12 μm).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…After 3 h of mixing, d50 was reduced to 4.4 μm, which was a full 3 times smaller than that of the sterile control group (17 μm). This suggested that the presence of bacteria may promote the dispersion of oil droplets, form droplets with smaller particle sizes, and enhance the interaction between kaolinite and oil droplets . However, after 24 h, the droplet size in the sample started to increase and d50 increased to about 5.5 μm, which was still smaller than d50 at 1 min (12 μm).…”
Section: Resultsmentioning
confidence: 97%
“…This suggested that the presence of bacteria may promote the dispersion of oil droplets, form droplets with smaller particle sizes, and enhance the interaction between kaolinite and oil droplets. 52 However, after 24 h, the droplet size in the sample started to increase and d50 increased to about 5.5 μm, which was still smaller than d50 at 1 min (12 μm). Similar results were found in other experimental groups.…”
Section: Spatial Structure Of Opas Under the Bacterial Actionmentioning
confidence: 86%
See 1 more Smart Citation
“…After completely covering the available surface area of the oil droplet, the continued growth of cells within the monolayer generates interfacial stresses that lead to the deformation of the oil-water interface. 25,26 To understand how interfacial growth stresses behave in a curved growing monolayer, it is crucial to first understand the alignment behavior of cells within the layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, a comprehensive picture of the mechanism of biofilm formation and its coupling to oil degradation remains unclear. To date, few studies have focused on the dynamics of OHCB biofilms formation at the oil-water interface at the micro-drop scale ( 2123 ). Nonetheless, these studies do not resolve the physical process of biofilm formation and oil degradation at the single-bacterium scale.…”
Section: Introductionmentioning
confidence: 99%